Rituals of Hunger. Laurie Halse Anderson’s Wintergirls - Szatanik, Zuzanna (Romanica Silesiana)
The following article discusses rituals of control and purification characteristic of anorexia and bulimia nervosa, as shown in Laurie Halse Anderson’s novel Wintergirls. One of the main assumptions of the paper is that eating disorders should be analyzed in the context of contemporary Western culture and the conventional models of femininity. As the Beauty Myth becomes the modern religion, rituals of hunger are interpreted as a present‑day version of religious rites. Key words: anorexia nervosa, bulimia nervosa, the Beauty Myth, rituals of control and purification